Effect of Class Attendance on Medical Student's Academic Performance - An Observational Study - Ahmad, Mushtaq; Rahman, Farial Naima; Shawon, Md Mozaharul Islam; Ali, Mohammad (Faridpur Medical College Journal, 2017)
This cross sectional study was conducted at Armed Forces Medical College (AFMC), Dhaka from October 2015 to September 2016. A total of 475 students belonged to four different phase groups were selected as research sample. Research Data regarding academic results and class attendance was collected from records of training section of the college and different departments. A pre tested semi structured questionnaire was distributed to the students to get their opinion regarding attendance and absence in the classes. Data was analyzed in terms of percentage and Chi- Square test using SPSS- 20 version of software. Male and female student ratio in this study was 168(35.36%): 307(64.64%). Majority of male students 142(84.52%) and female 282(91.86 %) obtained eligibility level of attendance. Considering item examinations 139(97.88%) male and 269(95.39%) female students completed the items in due time. Among students with good attendance male 133 (93.66%) and female 269(95.39%) passed the Term final exams regularly. In Professional examinations 128(90.14%) male and 261(92.55%) female students with better attendance passed at first chance. Statistically result by Chi-Square test showed significant result. Considering reasons for presence in the class 475(100%) students said it is a requirement for qualification to sit for professional MBBS examinations, 472(99.37%) attended to get clear idea about topic of discussion, 471(99.16%) opted for getting chance for interaction with class teacher, 468(98.53%) gave opinion about getting suggestions and important questions for examination, 412(86.74%) found the topic interesting and 67(14.11%) attended class for avoiding fine for absence. Regarding absence in the class 54(11.37%) was sick, 51(10.74%) found the class boring, 44(9.26%) felt the topic boring, 41(8.63%) was busy otherwise, 37(7.79%) thought they could get notes from friends, 22(4.63%) was on leave and 17(3.58%) thought they could pass subject without attending the classes. Students with regular attendance in class generally have positive effect since they get benefit from having better examination results, higher self concept, higher standardized test scores and educational attainment. Faridpur Med. Coll. J. Jul 2017;12(2): 58-63